Antiviral composite particle as well as screening method and application thereof
By screening antiviral composite particles, and using polymer and oligomeric metal salt particles to form composite particles, the problems of poor selectivity and high cytotoxicity of existing metal antiviral materials are solved, and a broad-spectrum and safe antiviral effect is achieved.
Patent Information
- Application Number
- CN202511161303.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-19
- Publication Date
- 2025-12-05
- Estimated Expiration
- 2045-08-19
AI Technical Summary
Existing metal antiviral materials have poor selectivity for viruses, and high concentrations can easily cause cytotoxicity to host cells, making it difficult to combine antiviral activity with biosafety.
This invention provides a method for screening antiviral composite particles, which utilizes the hybridization of polymer and oligomeric metal salt particles to form composite particles, regulates the coordination mode of the metal oligomers and the charge distribution of the polymer backbone to form an electrostatic barrier, selectively adsorbing viral particles without entering host cells.
It achieves broad-spectrum and safe antiviral activity, can significantly inhibit a variety of viruses, and maintains low cytotoxicity, providing a basis for the development of broad-spectrum and safe antiviral drugs and protective equipment.
Smart Images

Figure CN121059537A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the field of virus protection, and particularly relates to an anti-virus composite particle as well as a screening method and application thereof. BACKGROUND
[0002] Virus epidemics continue to threaten global public health safety, and traditional anti-virus strategies have obvious limitations. Small molecule anti-virus drugs (such as virus entry inhibitors fostemsavir, polymerase inhibitors favipiravir and sofosbuvir, etc.) act by targeting specific virus enzymes, but have two major core defects: one is that viruses can quickly develop drug resistance through genetic mutation; the other is that the action spectrum is narrow, making it difficult to cope with complex and variable virus mutations. This situation urgently needs to develop new preparations with broad-spectrum anti-virus activity, rather than traditional drugs targeting a single target.
[0003] Metal-based materials (such as silver, copper compounds) have unique potential in the field of anti-virus due to their inherent antibacterial properties. Existing metal anti-virus systems mainly fall into two categories: one is metal oxides (such as ZnO), which destroy virus macromolecules and cut off the disulfide bonds on the surface of virus particles by generating reactive oxygen species (ROS); the other is metal ions (such as Ag + , Cu 2+ ), which block the invasion of host cells by interacting with virus envelopes. However, these materials face a key bottleneck, i.e. poor selectivity for viruses, and high concentration use can easily cause toxicity to host cells, making it difficult to achieve both "anti-virus activity" and "biological safety". Therefore, there is an urgent need to develop an anti-virus material that has both anti-virus activity and biological safety. SUMMARY
[0004] To solve at least part of the technical problems in the prior art, the present application provides an anti-virus composite particle as well as a screening method and application thereof. Specifically, the present application includes the following contents.
[0005] In a first aspect of the present application, a method for screening an anti-virus composite particle is provided, which comprises the following steps: (1) providing a composite particle library, wherein the composite particle comprises a polymer and an oligomerized metal salt particle; (2) contacting a test composite particle in the composite particle library with a virus, and then detecting virus activity; and (3) when the virus activity is reduced after the test composite particle is contacted with the virus, the test composite particle is taken as an anti-virus composite particle.
[0006] In certain embodiments, the method for screening an anti-virus composite particle according to the present application, wherein the composite particle library comprises a polymer library P and an oligomerized metal salt particle library M, and the polymers P in the polymer libraryx oligomerized metal salt particles M in the oligomerized metal salt particle library y capable of hybridization to form composite particles P x M y .
[0007] In some embodiments, the method for screening antiviral composite particles according to the present application, wherein the polymer comprises a hydrophilic block and a hydrophobic block.
[0008] In some embodiments, the method for screening antiviral composite particles according to the present application, wherein the monomers of the hydrophobic block of the polymer comprise metal-binding monomers and branched side chain monomers, and the metal-binding monomers comprise amino groups and / or hydroxyl groups; the branched side chain monomers are selected from at least one of DMA, DEA, EPA, DPA, DBA, and DAA.
[0009] In some embodiments, the method for screening antiviral composite particles according to the present application, wherein the metal in the oligomerized metal salt is selected from at least one of magnesium, calcium, chromium, cobalt, copper, and zinc.
[0010] In some embodiments, the method for screening antiviral composite particles according to the present application, wherein step (2) comprises adding the composite particles to be tested and viruses to a cell model, and measuring the viral inhibition rate and / or cell survival rate.
[0011] In a second aspect of the present application, there is provided an antiviral composite particle prepared by the method of the first aspect of the present application.
[0012] In some embodiments, the antiviral composite particle according to the present application, wherein the antiviral composite particle comprises PAMO-DPA / Cu.
[0013] In a third aspect of the present application, there is provided an antiviral composition comprising the antiviral composite particle of the second aspect of the present application and a pharmaceutically acceptable carrier.
[0014] In a fourth aspect of the present application, there is provided use of the antiviral composite particle according to the second aspect of the present application in the preparation of an antiviral drug, coating, or protective equipment.
[0015] The present application utilizes the reversible hydrogen bond network of polymers (such as polyacrylates) with both hydrophilic and hydrophobic properties to precisely control the coordination mode of metal oligomers, and balances the dispersibility and virus capture capacity of the material by adjusting the charge distribution of the polymer backbone, and controls the surface potential to form an electrostatic barrier on the surface of the material, so that the material selectively adsorbs virus particles without entering host cells, avoiding the induction of intracellular toxicity.
[0016] In addition, the application breaks through the dilemma of "activity-toxicity" of traditional metal-based materials through the synergistic design of controllable assembly of metal oligomers and polymer interface engineering, and provides strong support for the development of broad-spectrum, safe antiviral drugs, coatings, protective equipment, etc. BRIEF DESCRIPTION OF DRAWINGS
[0017] Figure 1 Exemplary shows the screening process of the antiviral composite particles, wherein A is the Zeta potential, particle size and polydispersity index of the oligomerized metal salt; B is the Zeta potential of the polymer; C is the synthesis path diagram of the oligomerized metal salt PAMO-Metal, the polymer PAMO-Polymer and the composite particles PAMO-Polymer / Metal, M represents different metals, and R represents different alkyl side chains; D is the Zeta potential, particle size and polydispersity index of the composite particles; E is the Zeta potential of the PAMO-Polymer / Cu composite particles; F is the infrared spectrum analysis result of PAMO-DPA / metal; G is the scanning electron microscope (SEM) image of PAMO-DPA / metal.
[0018] Figure 2 Exemplary shows the antiviral screening process of the composite particles PAMO-Polymer / Metal, wherein A is a PAMO-DPA / Metal combination library screening schematic diagram; B is the inhibitory effect of PAMO-DPA / Metal on RNA virus VSV-GFP; C is the inhibitory effect of PAMO-DPA / Metal on DNA virus HSV; D is a PAMO-Polymer / Cu combination library screening schematic diagram; E is the inhibitory effect of PAMO-Polymer / Cu on VSV-GFP virus; F and G respectively show the inhibitory effect of PAMO-DPA / Cu on mouse hepatitis virus and Sendai virus.
[0019] Figure 3 A of exemplary shows the half maximal inhibitory concentration (IC50) analysis of PAMO-Polymer / Cu; B shows the cytotoxicity heat map analysis of PAMO-Polymer / Cu; C shows the antiviral dose-effect heat map of PAMO-Polymer / Cu; D shows the comprehensive evaluation of the efficacy and toxicity of PAMO-Polymer / Cu system.
[0020] Figure 4 Exemplary shows the in vivo antiviral effect and safety evaluation of PAMO-DPA / Cu, wherein A shows the schematic diagram of the virus infection model construction and the drug administration scheme of the experimental mice; B shows the influence of drug administration on the survival cycle of the infected mice; C-D show the virus load detection results of the target organs; E shows the liver pathological analysis results; F shows the multi-organ histopathological analysis results.
[0021] Figure 5Results of dose-dependent safety evaluation of the antiviral composite particles of the present application are shown.
[0022] Figure 6 Effects of different ratios of hydrogen bond donors and acceptors on the performance of PAMO-DPA / Cu are shown, wherein A is a schematic diagram of the hydrogen bonding mechanism in PAMO-DPA / Cu; B is the dispersion state of PAMO-DPA / Cu under different ratios of hydrogen bond donors and acceptors; C is the polydispersity index of PAMO-DPA / Cu under different ratios of hydrogen bond donors and acceptors; D is the particle size distribution characteristics of PAMO-DPA / Cu under different ratios of hydrogen bond donors and acceptors; and E is the time-dependent effect of different ratios of hydrogen bond donors and acceptors on antiviral activity. DETAILED DESCRIPTION
[0023] Various exemplary embodiments of the present application will now be described in detail, which should not be considered as limiting the present application, but rather as a more detailed description of certain aspects, characteristics and embodiments of the present application.
[0024] It should be understood that the terms used in the present application are merely for the description of specific embodiments, and are not intended to limit the present application. In addition, for the numerical ranges in the present application, it should be understood that the upper limit and the lower limit of the range and every intermediate value between them are specifically disclosed. Every smaller range within the range of any stated value or stated range, as well as any other stated value or intermediate value within the stated range, is also included in the present application. The upper limit and the lower limit of these smaller ranges can be included or excluded independently from the range.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. Although methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present application, the preferred methods and materials are described. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials in connection with which the documents are cited. In the case of conflict between any document incorporated by reference and the present specification, the present specification will control.
[0026] Method of screening antiviral complex particles In one aspect of the present application, a method for screening antiviral composite particles is provided, which comprises steps (1)-(3): (1) providing a composite particle library, wherein the composite particles comprise a polymer and an oligomerized metal salt particle; (2) contacting the test composite particles in the composite particle library with a virus, and then detecting viral activity; and (3) when the viral activity is reduced after the test composite particles are contacted with the virus, the test composite particles are used as antiviral composite particles.
[0027] The following describes each step in detail.
[0028] Step (1) of the method of the present application is a step of providing a library of composite particles, wherein the composite particles comprise a polymer and an oligomerized metal salt particle.
[0029] In a preferred embodiment, the library of composite particles is provided by the following method: (I) reacting metal ions (examples of which include, but are not limited to, copper, calcium, magnesium, cobalt, zinc, chromium, silver, rare earth metal ions, etc.) and an inorganic acid (preferably an acid that forms a slightly soluble or insoluble salt with the metal ion, such as, but not limited to, phosphoric acid, sulfuric acid, carbonic acid, etc.) in the presence of an oligomerization initiator (examples of which include, but are not limited to, triethylamine, trimethylamine (TMA), tripropylamine (TPA), pyridine, N-methylmorpholine, choline, tetramethylammonium hydroxide, etc.) to obtain a library of oligomerized metal salts; (II) polymerizing a hydrophilic block (such as, but not limited to, polyethylene glycol, PVP, polyamino acid, etc.), a metal-binding monomer (a monomer containing an amino group and / or a hydroxyl group, such as, but not limited to, AMA, lysine, etc.), and a branched side chain monomer (such as, but not limited to, DMA, DEA, EPA, DPA, DBA, DAA, etc.) in the presence of an initiator to obtain a library of polymers; (III) hybridizing the oligomerized metal salt and the polymer to obtain the library of composite particles.
[0030] In order to make the composite particles have more excellent antiviral effects, the amounts of the oligomerized metal salt obtained in step (I) and the polymer obtained in step (II) can be controlled so that the ratio of hydrogen bond donors in the polymer to hydrogen bond acceptors in the oligomerized metal salt is within a suitable range. In the present application, the ratio of hydrogen bond donors to hydrogen bond acceptors is 1:(1-15), preferably 1:(2-14), more preferably 1:(3-13), and even more preferably 1:(4-12), such as 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12.
[0031] In another preferred embodiment, the composite particle library is provided by: (I) dissolving copper chloride dihydrate (0.5-5 g) in anhydrous ethanol, adding triethylamine (5-30 mL), stirring at room temperature for 20-40 minutes, adding phosphoric acid ethanol solution (500-900 μL) dropwise, continuing to stir overnight, centrifuging (2,000-50,000 rpm, 5-20 minutes) to discard the supernatant, washing the precipitate with anhydrous ethanol for 3-10 times, and drying to obtain the oligomerized metal salt PAMO-Cu, and using the same method to prepare PAMO-Mg, PAMO-Ca, PAMO-Cr, PAMO-Co, PAMO-Zn to obtain the oligomerized metal salt particle library M; (II) reacting the hydrophilic polymer with 2-bromoisobutyryl bromide (BiBB) in the presence of triethylamine to obtain the Br-activated hydrophilic polymer, purifying by dialysis and freeze-drying, dissolving the Br-activated hydrophilic polymer, monomer DPA, AMA, cuprous bromide, azobisisobutyronitrile, and TPMA in a mixed solvent in proportion, bubbling argon to remove oxygen for 20-50 minutes, and reacting at 50-90°C in an oil bath for 30-70 hours to obtain the polymer PAMO-DPA, and using the same method to prepare PAMO-DMA, PAMO-DEA, PAMO-EPA, PAMO-DBA, and PAMO-DAA to obtain the polymer library P; (III) dissolving the polymer PAMO-DPA in dichloromethane, dispersing the oligomerized metal salt particle PAMO-Cu in anhydrous ethanol, mixing the two solutions in equal volume, stirring at room temperature overnight, removing the solvent by rotary evaporation, redissolving in ethanol / tetrahydrofuran, adding deionized water, and ultrasonic treatment to volatilize the organic solvent to obtain the PAMO-DPA / Cu composite particle, and using the same method to prepare PAMO-DPA / Mg, PAMO-DPA / Ca, PAMO-DPA / Cr, PAMO-DPA / Co, PAMO-DPA / Zn, PAMO-DMA / Cu, PAMO-DEA / Cu, PAMO-EPA / Cu, PAMO-DBA / Cu, and PAMO-DAA / Cu to obtain the composite particle library.
[0032] It can be understood that the oligomerized metal salt library, the polymer library, or the composite particle library can be subjected to particle size analysis, zeta potential analysis, polydispersity index analysis, and the like before detecting the antiviral activity of the composite particles for preliminary screening, and the order of the preliminary screening of the oligomerized metal salt library and the polymer library is not particularly limited, for example, the preliminary screening of the oligomerized metal salt library is performed first, then the preliminary screening of the polymer library is performed, or the preliminary screening of the polymer library is performed first, then the preliminary screening of the oligomerized metal salt library is performed, or both are performed simultaneously.
[0033] In the present application, the composite particle library includes the polymer library P and the oligomerized metal salt particle library M, and the polymer P in the polymer library x and the oligomerized metal salt particle M in the oligomerized metal salt particle libraryy Capable of hybridizing to form composite particles P x M y Polymer P x It refers to any polymer in the polymer library, M y It refers to any one type of oligomerizing metal salt particle in the oligomerizing metal salt particle library, P x M y This refers to composite particles formed by random hybridization combinations of any polymer and any oligomerized metal salt particles from the aforementioned library. In a preferred embodiment, the polymer library P includes PAMO-DMA, PAMO-DEA, PAMO-EPA, PAMO-DPA, PAMO-DBA, and PAMO-DAA. In a preferred embodiment, the oligomerized metal salt particle library M includes PAMO-Cu, PAMO-Mg, PAMO-Ca, PAMO-Cr, PAMO-Co, and PAMO-Zn. In a preferred embodiment, the composite particle library includes PAMO-DPA / Cu, PAMO-DPA / Mg, PAMO-DPA / Ca, PAMO-DPA / Cr, PAMO-DPA / Co, PAMO-DPA / Zn, PAMO-DMA / Cu, PAMO-DEA / Cu, PAMO-EPA / Cu, PAMO-DBA / Cu, and PAMO-DAA / Cu.
[0034] In this invention, the polymer comprises hydrophilic and hydrophobic blocks, wherein the hydrophilic blocks are derived from, but are not limited to, PEG; the monomers of the hydrophobic blocks comprise metal-bound monomers and branched side-chain monomers, and the metal-bound monomers contain amino and / or hydroxyl groups, examples of which include, but are not limited to, AMA; examples of the branched side-chain monomers include, but are not limited to, DMA, DEA, EPA, DPA, DBA, DAA, etc. In a preferred embodiment, the metal-bound monomer is AMA, the branched side-chain monomer is DPA, and the monomer of the hydrophilic block is PEG.
[0035] In this invention, the equivalent of the branched side chain monomer is 50-150, preferably 60-140, even more preferably 70-130, and more preferably 80-120, for example 80, 85, 90, 95, 100, 105, 110, 115, 120.
[0036] In this invention, the metal in the oligomerized metal salt is not particularly limited, and examples include, but are not limited to, magnesium, calcium, chromium, cobalt, copper, zinc, selenium, rare earth metals, etc.
[0037] Step (2) of the method of the present invention involves contacting the test composite particles in the composite particle library with the virus and then detecting viral activity. The method for detecting viral activity is not particularly limited, and examples include, but are not limited to, flow cytometry, real-time quantitative PCR, ELISA / Western Blot, plaque assay, and TCID50 determination. It is understood that the test composite particles and the virus can be added to a cell model, and the viral inhibition rate and cell viability can be measured. The method for detecting cell viability is not particularly limited, and examples include, but are not limited to, the CCK-8 assay, MTT assay, XTT assay, ATP assay, and Calcein-AM assay.
[0038] Step (3) of the present invention is to determine whether the composite particle to be tested is an antiviral composite particle. When the activity of the virus decreases after the composite particle to be tested comes into contact with the virus, the composite particle to be tested is regarded as an antiviral composite particle.
[0039] Antiviral complex particles In one aspect, the present invention provides an antiviral composite particle prepared by the method described herein. In a preferred embodiment, the antiviral composite particle comprises PAMO-DPA / Cu.
[0040] In this invention, the virus includes DNA viruses and / or RNA viruses. Examples of DNA viruses include, but are not limited to, herpes simplex virus (e.g., herpes simplex virus type 1, herpes simplex virus type 2), varicella-zoster virus, cytomegalovirus, smallpox virus, monkeypox virus, adenovirus, human papillomavirus, parvovirus, bocavirus, hepatitis B virus, etc.; examples of RNA viruses include, but are not limited to, vesicular stomatitis virus, mouse hepatitis virus, Sendai virus, encephalomyocytoxin virus, influenza A virus, influenza B virus, influenza C virus, dengue virus, Zika virus, Ebola virus, Marburg virus, Nipah virus, coronavirus, hepatitis A virus, hepatitis C virus, rotavirus, measles virus, human immunodeficiency virus, respiratory syncytial virus, rabies virus, etc. In one preferred embodiment, the DNA virus is herpes simplex virus. In another preferred embodiment, the RNA virus is vesicular stomatitis virus. In yet another preferred embodiment, the RNA virus is mouse hepatitis virus. In yet another preferred embodiment, the RNA virus is Sendai virus. In a preferred embodiment, the virus of the present invention is an enveloped virus.
[0041] In a preferred embodiment, the antiviral composite particles of the present invention can achieve a virus inhibition rate of not less than 90%, for example not less than 95%, or even more than 99%, while having a cell survival rate of not less than 95% in terms of cytotoxicity. Therefore, the antiviral composite particles of the present invention have both antiviral activity and biosafety.
[0042] Antiviral composition In one aspect, the present invention provides an antiviral composition comprising the antiviral complex particles described herein and a pharmaceutically acceptable carrier.
[0043] In this invention, pharmaceutically acceptable carriers are used to transport or deliver a drug from one organ or part of the body to another organ or part of the body. Each carrier is "acceptable," meaning it is compatible with other components of the formulation (e.g., antiviral complex particles) and does not harm the patient. The pharmaceutically acceptable carriers include at least one of diluents, fillers, absorbents, wetting agents, binders, disintegrants, lubricants, sweeteners, preservatives, and antioxidants. Examples of diluents include, but are not limited to, physiological saline, aqueous buffer solutions, solvents, and dispersion media; fillers include, but are not limited to, starch, lactose, mannitol, and microcrystalline cellulose; absorbents include, but are not limited to, calcium sulfate, dicalcium phosphate, and calcium carbonate; wetting agents include, but are not limited to, water and ethanol; binders include, but are not limited to, hydroxypropyl methylcellulose, povidone, and microcrystalline cellulose; disintegrants include, but are not limited to, croscarmellose sodium, croscarmellose, surfactants, and low-substituted hydroxypropyl cellulose; lubricants include, but are not limited to, magnesium stearate, talc, polyethylene glycol, sodium dodecyl sulfate, micronized silica gel, and talc; sweeteners include, but are not limited to, sucralose, acetylsupan, saccharin, sucrose, xylitol, mannitol, sorbitol, glucose, fructose, and aspartame; preservatives include, but are not limited to, parabens, chlorobutanol, phenol, and sorbic acid; and antioxidants include, but are not limited to, ascorbic acid and methionine.
[0044] Use This invention further provides the use of the composite particles in the preparation of antiviral drugs, coatings, or protective equipment. The coatings include, but are not limited to, coatings for medical devices, public facilities, household goods, and personal items. The protective equipment includes, but is not limited to, medical masks, protective suits, medical gloves, and respirators.
[0045] In this invention, antiviral action is achieved by administering a therapeutically effective amount of the antiviral drug to the subject. Subjects include, but are not limited to, mammals, including but not limited to, humans, mice, rabbits, cats, dogs, cattle, sheep, and pigs.
[0046] In this invention, there are no particular limitations on the method of administration of the drug. Representative methods of administration include, but are not limited to, oral, rectal, parenteral (intravenous, intramuscular, or subcutaneous) and local administration. Accordingly, the drug of this invention can be formulated into various clinically acceptable dosage forms, including oral dosage forms, injectable dosage forms, local dosage forms, or topical dosage forms.
[0047] The therapeutically effective dose described in this invention refers to a pharmaceutically recognized effective dosage, meaning that the amount of the active compound (i.e., the compound granules) is sufficient to significantly improve the condition without causing serious side effects. The daily dosage of the compound granules is typically 0.01-1,000 mg / kg, preferably 0.01-500 mg / kg, or 0.01-400 mg / kg, or 0.01-300 mg / kg, or 0.01-200 mg / kg, or 0.01-150 mg / kg, or 0.01-100 mg / kg, or 0.01-50 mg / kg, or 0.01-40 mg / kg, or 0.01-30 mg / kg, with 0.01-20 mg / kg being the most preferred. Exemplary effective dosages include, for example, 0.01 mg / Kg, 0.05 mg / Kg, 0.1 mg / Kg, 0.2 mg / Kg, 0.3 mg / Kg, 0.4 mg / Kg, 0.5 mg / Kg, 0.75 mg / Kg, 0.95 mg / Kg, 1 mg / Kg, 1.25 mg / Kg, 1.5 mg / Kg, 1.75 mg / Kg, 2 mg / Kg, 2.5 mg / Kg, 2.75 mg / Kg, 3 mg / Kg, 3.25 mg / Kg, 3.5 mg / Kg, 3.75 mg / Kg, 4 mg / Kg, 4.25 mg / Kg, 4.5 mg / Kg, 4.75 mg / Kg, 5 mg / Kg, 5.25 mg / Kg, 5.5 mg / Kg, 5.75 mg / Kg, 6 mg / Kg, and 6.25 mg / Kg. The recommended doses are: 6.5 mg / kg, 6.75 mg / kg, 7 mg / kg, 7.25 mg / kg, 7.5 mg / kg, 7.75 mg / kg, 8 mg / kg, 8.25 mg / kg, 8.5 mg / kg, 8.75 mg / kg, 9 mg / kg, 9.25 mg / kg, 9.5 mg / kg, 9.75 mg / kg, 10 mg / kg, 11 mg / kg, 12 mg / kg, 13 mg / kg, 14 mg / kg, 15 mg / kg, 16 mg / kg, 17 mg / kg, 18 mg / kg, 19 mg / kg, and 20 mg / kg. These doses can be administered as a single daily dose, divided into multiple daily doses, or at intervals.
[0048] Example 1 This embodiment exemplifies a screening method for antiviral composite particles. In this embodiment, PAMO is a polyacrylate-metal oligomer, also known as a polyacrylate-metal oligomer; PAMO-Polymer is a polymer; PAMO-Metal is an oligomerized metal salt, also known as a metal oligomer; PAMO-Polymer / Metal is a composite particle; DMA is 2-(dimethylamino)ethyl methacrylate; DEA is 2-(diethylamino)ethyl methacrylate; EPA is 2-(ethylpropylamino)ethyl methacrylate; DPA is 2-(dipropylamino)ethyl methacrylate; DBA is 2-(dibutylamino)ethyl methacrylate; DAA is 2-(dipentylamino)ethyl methacrylate; and AMA is 2-aminoethyl methacrylate.
[0049] 1. Construction of composite particle library 1.1 Materials and Laboratory Animals The calcium chloride dihydrate (CaCl2), cobalt chloride hexahydrate (CoCl2), chromium chloride (CrCl2), copper chloride dihydrate (CuCl2), magnesium chloride hexahydrate (MgCl2), and zinc chloride (ZnCl2) used in the experiment were purchased from Aladdin or Anaiji Chemical; triethylamine (TEA), phosphoric acid (H3PO4), and other organic solvents were purchased from Beijing Tongguang Fine Chemical; the cell counting kit (CCK-8) was purchased from TargetMol; the reverse transcription and quantitative PCR kit was purchased from AbClonal; paraformaldehyde fixative and RNA / DNA extraction reagents were purchased from Beijing Solarbio; and fluorescent dyes were purchased from Beyotime.
[0050] BALB / c mice aged 6-8 weeks were used as experimental animals and housed in an environment with a temperature of 20-26℃, humidity of 40-70%, and a 12-hour light-dark cycle. The animal experimental protocol was approved by the Ethics Committee of Peking University School of Medicine (No.: DLASBD0605).
[0051] 1.2 Experimental Methods 1.2.1 Preparation of oligomerized metal salt particle library Copper chloride dihydrate (1.70 g, 10 mmol) was dissolved in anhydrous ethanol, and triethylamine (14 mL) was added. The mixture was stirred at room temperature for 30 minutes, and 700 μL of phosphate ethanol solution was added dropwise. The mixture was stirred overnight, centrifuged (10,000 rpm, 10 minutes), and the supernatant was discarded. The precipitate was washed five times with anhydrous ethanol and dried to obtain the oligomerized metal salt PAMO-Cu. PAMO-Mg, PAMO-Ca, PAMO-Cr, PAMO-Co, and PAMO-Zn were prepared using the same method to obtain the oligomerized metal salt particle library M. Dynamic light scattering (DLS) analysis was performed, and the results are as follows: Figure 1As shown in Figure A, the particle size distribution of PAMO-Metal is in the range of 100-160 nm. The polydispersity index (PDI) exhibited by PAMO-Cu indicates its excellent stability. The zeta potential analysis results can be used to evaluate the cell binding ability of oligomeric metal salt particles and subsequent therapeutic effects.
[0052] 1.2.2 Preparation of Polymer Library Polyethylene glycol (PEG) reacts with 2-bromoisobutyryl bromide (BiBB) in the presence of triethylamine to generate PEG-Br, which is purified by lyophilization by dialysis and then used for later use.
[0053] PEG-Br (1 equivalent), monomer DPA (100 equivalent), AMA, cuprous bromide, azobisisobutyronitrile (AIB), and TPMA were dissolved in a DMF / isopropanol (1:1) mixed solvent in a specific ratio. The mixture was deoxygenated by argon bubbling for 30 minutes and reacted in an oil bath at 70°C for 48 hours to obtain the polymer PAMO-DPA. PAMO-DMA, PAMO-DEA, PAMO-EPA, PAMO-DBA, and PAMO-DAA were prepared using the same method, resulting in polymer library P. By precisely controlling the hydrophobic block structure, six polymers with different side chain lengths (i.e., PAMO-DMA, PAMO-DEA, PAMO-EPA, PAMO-DBA, PAMO-DPA, and PAMO-DAA) were successfully synthesized. The monomer structures and reaction products were confirmed using ¹H NMR spectroscopy. Chemical shift changes in the range of 3.2–0.4 ppm confirmed the precise construction of the target polymer structures. Zeta potential analysis was performed on different polymers, and the results are as follows: Figure 1 As shown in B, the weak positive charge exhibited by PAMO-DPA indicates that it has better safety characteristics.
[0054] 1.2.3 Preparation of composite particles The polymer PAMO-DPA was dissolved in dichloromethane, and the oligomerized metal salt particles PAMO-Cu were dispersed in anhydrous ethanol. Equal volumes of the two solutions were mixed and stirred overnight at room temperature. The solvent was removed by rotary evaporation, and the mixture was reconstituted in ethanol / tetrahydrofuran. Deionized water was then added, and the mixture was sonicated to evaporate the organic solvent, yielding PAMO-DPA / Cu composite particles. PAMO-DPA / Mg, PAMO-DPA / Ca, PAMO-DPA / Cr, PAMO-DPA / Co, PAMO-DPA / Zn, PAMO-DMA / Cu, PAMO-DEA / Cu, PAMO-EPA / Cu, PAMO-DBA / Cu, and PAMO-DAA / Cu were prepared using the same method, resulting in a composite particle library. A schematic diagram of the composite particle synthesis is shown below. Figure 1 As shown in C.
[0055] Dynamic light scattering analysis results are as followsFigure 1 As shown in Figure D, the average particle size of PAMO-DPA / Metal is significantly reduced to 30-60 nm, exhibiting better stability. In particular, the PDI values of PAMO-DPA / Ca and PAMO-DPA / Cu are reduced, confirming that polymer coupling improves dispersibility. Notably, the PAMO-DPA / Metal system as a whole is positively charged, with PAMO-DPA / Ca and PAMO-DPA / Cu exhibiting relatively low zeta potentials, which are beneficial for improving biocompatibility. The zeta potential of PAMO-Polymer / Cu is shown in Figure D. Figure 1 As shown in Figure E, PAMO-DPA / Cu exhibits the lowest zeta potential and lower surface cytotoxicity. Infrared spectroscopy and scanning electron microscopy (SEM) analysis of PAMO-DPA / Metal yielded the following results: Figure 1 As shown in F and G.
[0056] 2. Evaluation of antiviral activity 2.1 Evaluation of the antiviral activity of PAMO-DPA / Metal In the A549 cell model, after treating VSV-GFP virus with 0.01 multiplicity of infection (MOI) and 250 μM PAMO-DPA / Metal for 24 hours, the viral infection status was observed and analyzed by flow cytometry. The results are as follows: Figure 2 As shown in Figure B, the evaluation of VSV-GFP (RNA virus) in A549 cells showed that PAMO-DPA / Cu exhibited the best antiviral effect, which was also verified in HeLa cells.
[0057] In the HeLa cell model, 0.1 MOI HSV virus was simultaneously treated with 500 μM PAMO-DPA / Metal for 48 hours, and the viral infection efficiency was assessed by quantitative PCR. Results are as follows: Figure 2 As shown in Figure C, metals such as calcium, chromium, cobalt, and copper exhibit significant antiviral effects. Among all PAMO-DPA / Metal composite particles, PAMO-DPA / Cu showed significant inhibitory effects against both RNA and DNA viruses.
[0058] 2.2 Evaluation of the antiviral activity of PAMO-Polymer / Cu In the A549 cell model, after co-treatment with 0.01 MOI VSV virus and 250 μM composite particles for 24 hours, the viral infection status was observed and analyzed by flow cytometry. The results are as follows: Figure 2As shown in Figure E, PAMO-DMA / Cu, PAMO-DEA / Cu, PAMO-EPA / Cu, and PAMO-DPA / Cu exhibited significant antiviral activity in A549 cells, and this result was consistent in HeLa cells.
[0059] 4T1 cells were co-treated with MHV-A59 virus (0.1 MOI) and co-particles for 48 hours, and viral RNA levels were detected by qPCR. HeLa cells were co-treated with different SeV strains (0.1 MOI) and co-particles for 48 hours, and viral RNA levels were detected by qPCR. Results are as follows: Figure 2 As shown in F and G, PAMO-DPA / Cu exhibits excellent inhibitory effects against RNA viruses such as mouse hepatitis virus (MHV) and Sendai virus (SeV), with antiviral efficiency consistently exceeding 90%, and in most cases approaching complete inhibition (100%).
[0060] This embodiment further investigated the subcellular localization of the polymer and composite particles. The results showed that PAMO-DPA was mainly localized intracellularly under all conditions, while PAMO-DPA / Cu was significantly enriched in the cell membrane region, showing a strong tendency to bind to the membrane. PAMO-DPA / Cu mainly exerted its direct antiviral effect through the extracellular pathway.
[0061] This embodiment also investigated the virus adsorption and nucleic acid adsorption capabilities of PAMO-DPA / Cu. Therefore, it was found that PAMO-DPA / Cu has a dual mechanism of action. On the one hand, the electrostatic interaction between the weak positive charge of the composite particles and the negative charge of the cell membrane forms an extracellular barrier, blocking the virus invasion pathway and shielding the virus binding receptors on the cell surface. It also effectively adsorbs free virus particles, promoting their clearance from the extracellular environment. On the other hand, the synergistic effect of DPA and copper oligomers enables the positively charged composite particles to adsorb negatively charged virus particles. By extracting negatively charged nucleic acids from the virus, its structural integrity is disrupted, thereby exerting potent antiviral activity.
[0062] 3. Cytotoxicity evaluation The survival rate of A549 cells was determined by a 24-hour cytotoxicity assay, and the results are as follows: Figure 3 As shown in Figure A, among the different PAMO-Polymer / Cu composite particles, PAMO-DPA / Cu exhibited the lowest cytotoxicity, with its IC50 value being significantly better than other composite particles. PAMO-DPA / Cu also demonstrated the best safety in HeLa cells.
[0063] Cytotoxicity thermogram analysis of PAMO-Polymer / Cu composite particles was performed. Cell survival status under different concentration treatments was visualized using a color gradient: yellow (value 1) represents high cell activity, and purple (value 0) indicates decreased cell survival. The results are as follows: Figure 3 As shown in B.
[0064] Antiviral dose-response heatmap analysis was performed on PAMO-Polymer / Cu composite particles. A color gradient was constructed based on the VSV-GFP viral infection rate: yellow (value 1) corresponds to low infection rate, and purple (value 0) reflects high infection rate, visually demonstrating the concentration-dependent antiviral effect of the nanoparticles. The results are as follows: Figure 3 As shown in C.
[0065] A comprehensive efficacy-toxicity assessment was performed on PAMO-Polymer / Cu composite particles. Specifically, six candidate composite particles were evaluated in three dimensions: electrical potential intensity was graded using signs "- / + / ++" (<10 for -, 10-20 for +, >20 for ++); cytotoxicity was graded into five levels based on IC50 values (<10 for +++, <100 for ++, 100-300 for +, 300-400 for -, >400 for --); antiviral efficiency was divided into three levels based on fluorescence microscopy observation and EC50 values (completely no fluorescence and EC50 <200 for +++, completely no fluorescence but EC50 >200 for ++, and weakened but not disappeared fluorescence for +). The results are as follows: Figure 3 As shown in D, PAMO-DPA / Cu maintains +++ level antiviral efficacy while exhibiting the lowest cytotoxicity characteristics, demonstrating the best overall performance.
[0066] In summary, DMA, DEA, and EPA polymers exhibit significant cytotoxicity due to their high positive charge; DBA and DAA polymers, on the other hand, show insufficient antiviral activity. Notably, PAMO-DPA / Cu demonstrates the lowest cytotoxicity while maintaining the highest antiviral activity.
[0067] 4. Evaluation of antiviral efficacy and safety in vivo 4.1 In vivo antiviral activity Six- to eight-week-old BALB / c mice were used to establish an MHV-A59 infection model via intraperitoneal injection on day 0. Two days post-infection (day 2), mice were treated with PAMO-DPA / Cu at a dose of 5 mg / kg. At the experimental endpoint on day 4, liver and spleen tissues were collected for viral titer determination and pathological damage assessment. A schematic diagram of the viral infection model construction and drug administration regimen for the experimental mice is shown below. Figure 4 As shown in A.
[0068] The effect of drug administration on the survival time of infected mice is as follows: Figure 4As shown in B, PAMO-DPA / Cu treatment significantly prolonged the survival time of infected mice.
[0069] Target organ viral load test results as follows Figure 4 As shown in the CD, the level of MHV viral RNA in the liver tissue of the PAMO-DPA / Cu treatment group was significantly reduced, and the viral load in the spleen tissue decreased even more significantly. The results indicate that PAMO-DPA / Cu composite particles have a significant antiviral effect.
[0070] Histopathological examination results as follows Figure 4 As shown in Figure E, the untreated group of mice exhibited typical characteristics of viral liver injury, while the liver tissue structure of the PAMO-DPA / Cu composite granule treatment group remained intact, with no obvious pathological changes observed. This indicates that the drug has a protective effect against viral liver injury and can effectively alleviate liver damage caused by MHV infection. Therefore, PAMO-DPA / Cu has a significant antiviral therapeutic effect in vivo.
[0071] Multi-organ histopathological analysis was performed. Using hematoxylin-eosin (HE) staining, the pathological morphological characteristics of the heart, liver, spleen, lungs, kidneys, and brain tissues of mice in different dosage groups were systematically observed on day 7 to comprehensively assess the in vivo safety of the drug. Results are as follows: Figure 4 As shown in Figure F, the composite particles did not cause significant damage to vital organs such as the heart, liver, spleen, lungs, kidneys, and brain, fully demonstrating their excellent in vivo safety.
[0072] 4.2 In vivo safety To assess the dose-dependent safety of the drug, normal mice were intravenously injected with saline, therapeutic dose, and 5-fold and 10-fold doses of PAMO-DPA / Cu composite granules. Seven days later, serum samples were collected to detect ALT, AST, ALP, UA, UREA, CREA, LDH, and CK. ALT (alanine aminotransferase), AST (aspartate aminotransferase), and ALP (alkaline phosphatase) reflect liver function; UA (uric acid), UREA (urea), and CREA (creatinine) characterize renal metabolic function; and LDH (lactate dehydrogenase) and CK (creatine kinase) serve as markers of myocardial injury.
[0073] The result is as follows Figure 5 As shown, after 7 days of treatment with the therapeutic dose and at 5 times and 10 times the dose, no significant abnormalities were observed in liver function (ALT, AST, ALP), kidney function (UA, UREA, CREA), and cardiac function indicators (LDH, CK) in any group of mice.
[0074] Example 2 This embodiment illustrates the effect of different ratios of hydrogen bond donors and acceptors on the properties of PAMO-DPA / Cu.
[0075] This embodiment measured the dispersion state, polydispersity index, particle size distribution characteristics, and time-dependent effects of different hydrogen bond donor-acceptor ratios on PAMO-DPA / Cu. A schematic diagram of the hydrogen bond interaction mechanism of PAMO-DPA / Cu is shown below. Figure 6 As shown in A, the amino hydrogen atom of PAMO-DPA acts as a hydrogen bond donor, and the phosphate group of PAMO-Cu acts as a hydrogen bond acceptor, achieving structural connection through a hydrogen bond network.
[0076] The dispersion states of PAMO-DPA / Cu with different hydrogen bond donor-acceptor ratios are as follows: Figure 6 As shown in B, when the hydrogen bond donor-acceptor ratio reaches 1:40 and 1:20, the solution exhibits obvious stratification, while at a ratio of 1:10, it presents a uniform dispersion system.
[0077] The effect of different hydrogen bond donor-acceptor ratios on the polydispersity index of PAMO-DPA / Cu is as follows: Figure 6 As shown in C, the 1:10 ratio system has the lowest polydispersity coefficient, and the polydispersity coefficient gradually increases with the increase of the hydrogen bond acceptor ratio.
[0078] The effect of different hydrogen bond donor-acceptor ratios on the particle size distribution characteristics of PAMO-DPA / Cu is as follows: Figure 6 As shown in D, the 1:10 ratio exhibits a single-peak narrow distribution; the 1:20 ratio shows a double-peak distribution; and the 1:40 ratio shows a multi-peak wide distribution with a significantly increased particle size, making it prone to sedimentation.
[0079] HeLa cells were co-treated for 24 hours with fresh / one-week-old PAMO-DPA / Cu (treatment concentration 500 μM) and VSV-GFP virus (0.01 MOI) at different hydrogen bond donor-acceptor ratios. Cell viability was detected by flow cytometry. Results are as follows: Figure 6 As shown in E, only the 1:10 ratio system maintained significant antiviral activity after one week of storage.
[0080] This invention effectively addresses the core issues of traditional antiviral strategies, such as limitations in their spectrum and the potential for drug resistance, by integrating metal ion oligomers with functional polymer materials. The invention achieves precise control over reaction conditions and structural characteristics by separately preparing polyacrylate precursors and metal ion oligomers, followed by a coupling reaction to construct a composite system. This effectively avoids the side reactions and uneven cross-linking problems common in direct polymerization methods. The self-assembly mechanism driven by dynamic hydrogen bonding interactions forms a nanostructure with controllable morphology and uniform size. These structural characteristics play a decisive role in enhancing the functional properties and antiviral efficacy of the composite particles.
[0081] At the molecular level, the cross-linked network of polyacrylate and metal ion oligomers achieves homogeneous fusion of organic and inorganic components, fundamentally solving the phase separation and interfacial compatibility problems commonly found in traditional organic-inorganic composites. The introduction of acrylate groups significantly enhances the water solubility, surface charge tunability, and physical stability of the oligomers, making them more suitable for biological systems. The optimized PAMO-DPA / Cu formulation exhibits broad-spectrum antiviral activity against various viruses, including VSV, MHV, HSV, and SeV.
[0082] This invention utilizes a comprehensive screening system combining an inorganic metal element oligomer library and an acrylate homologue library to identify copper-based PAMO-DPA as the optimal candidate, achieving the highest antiviral efficacy while maintaining the lowest cytotoxicity. The screening process also reveals structure-activity relationships, such as the correlation between side chain length and toxicity / efficacy, and the influence of polymer charge on viral activity, providing important theoretical basis for future antiviral drug development.
[0083] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. An antiviral complex particle, characterized in that, The antiviral composite particle is formed by hybridization of a polymer and an oligomerized metal salt particle.
2. The antiviral composite particle of claim 1, wherein, The polymer comprises a hydrophilic block and a hydrophobic block.
3. The antiviral composite particle of claim 2, wherein, The monomer of the hydrophobic block of the polymer comprises a metal-binding monomer and a branched side chain monomer, and the metal-binding monomer comprises an amino group and / or a hydroxyl group; the branched side chain monomer is selected from at least one of 2-(dimethylamino)ethyl methacrylate, 2-(diethylamino)ethyl methacrylate, 2-(ethylpropylamino)ethyl methacrylate, 2-(dipropylamino)ethyl methacrylate, 2-(dibutylamino)ethyl methacrylate, 2-(diamylamino)ethyl methacrylate, and 2-aminoethyl methacrylate.
4. The antiviral composite particle of claim 1, wherein, The metal in the oligomerized metal salt is selected from at least one of magnesium, calcium, chromium, cobalt, copper, and zinc.
5. The antiviral composite particle of claim 1, wherein, The antiviral composite particle comprises PAMO-DPA / Cu.
6. An antiviral composition, characterized by, The antiviral composite particle of any one of claims 1-5 and a pharmaceutically acceptable carrier.
7. Use of the antiviral composite particle of any one of claims 1-5 in the preparation of an antiviral drug, coating, or protective equipment.
8. A method for screening antiviral complex particles, characterized by, The method comprises the following steps: (1) providing a composite particle library, wherein the composite particle comprises a polymer and an oligomerized metal salt particle; (2) contacting a to-be-tested composite particle in the composite particle library with a virus, and then detecting viral activity; and (3) when the viral activity is reduced after the to-be-tested composite particle is contacted with the virus, the to-be-tested composite particle is taken as an antiviral composite particle. Preferably, the library of composite particles comprises a library of polymers P and a library of oligomerized metal salt particles M, and the polymers P in the library of polymers x are capable of hybridizing to form composite particles P y with the oligomerized metal salt particles M x in the library of oligomerized metal salt particles y ; Preferably, the metal in the oligomerized metal salt is selected from at least one of magnesium, calcium, chromium, cobalt, copper, and zinc.
9. The method for screening the antiviral complex granule according to claim 8, wherein, The polymer comprises a hydrophilic block and a hydrophobic block. Preferably, the monomer of the hydrophobic block of the polymer comprises a metal-binding monomer and a branched side chain monomer, and the metal-binding monomer comprises an amino group and / or a hydroxyl group; the branched side chain monomer is selected from at least one of 2-(dimethylamino)ethyl methacrylate, 2-(diethylamino)ethyl methacrylate, 2-(ethylpropylamino)ethyl methacrylate, 2-(dipropylamino)ethyl methacrylate, 2-(dibutylamino)ethyl methacrylate, 2-(diamylamino)ethyl methacrylate, and 2-aminoethyl methacrylate.
10. The method for screening the antiviral complex granule according to claim 8, wherein, Step (2) comprises adding the to-be-tested composite particle and the virus to a cell model, and measuring viral inhibition rate and / or cell survival rate.
Citation Information
Patent Citations
Hybrid particle made of polymers and nanoparticles
CN102753618A
Composite particles and methods of forming the same
CN115697906A
Antibacterial and antiviral polymer as well as preparation method and application thereof
CN116655846A
Preparation method of hybridized metal nano-particle
CN1686647A
Anti-viral pharmaceutical compositions
CN1946410A